Depiction of Natesha on the Bhadra of the Temple - Temples of India Project Team (Jio Institute, 2024)
The bhadra (central projection) of the temple, within the Triple-shrine Temple to the northwest of Mahanaleshwar Temple, has ornamental features. The jangha (wall) portion of the bhadra has a Natesha image framed in a decorative niche. The niche is made up of two pilasters that support a pediment. The pediment is composed of gavaksha (dormer window) motifs. The four-handed icon of Natesha icon is shown holding attributes like a trishula (trident) and a damru (hourglass-shaped drum). The jatamukuta (matted hairdo) of the icon is very peculiar.